An Integrative Review of Project Portfolio Management Literature: Thematic Findings on Sustainability Mindset, Assessment, and Integration - Aghajani, M.; Ruge, Gesa; Jugdev, K. (2023)
Sustainability integration in project portfolio management helps shape strategic, organizational, and project-based contexts. The authors conducted a structured literature review from 2000 to 2021 and developed a novel integrative framework presenting a holistic view highlighting three substantive research themes: sustainability mindset, sustainability assessment, and sustainability integration in project portfolio processes. Noteworthy progress has been made at the strategic and portfolio levels toward framing a sustainability mindset (definition, values, and principles) and developing frameworks/tools for sustainability assessment and project portfolio selection. However, areas for more research include integrating sustainability into project portfolio processes, reporting, and organizational learning for portfolio improvement.